2008
DOI: 10.1002/rcm.3872
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative confirmation procedure for ephedrines as acetonide derivatives in doping urine samples by gas chromatography/electron ionization mass spectrometry

Abstract: Ephedrines are sympathomimetic amines which have central nervous system stimulating properties and, for this reason, some of them are forbidden in sport by the World Antidoping Agency (WADA). They are screened and quantitated in urine by several published techniques and confirmed by gas chromatography/mass spectrometry (GC/MS). In this paper, a simple and easy confirmation procedure for norpseudoephedrine, norephedrine, ephedrine and pseudoephedrine in human urine by GC/electron ionization (EI)-MS is described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…These techniques have usually been applied to pharmacokinetics investigations and are not generally available in analytical laboratories, despite their high detection power. The method most widely used for assay of the isomers is high-performance liquid chromatography coupled with UV detection (LC-UV) [16][17][18][19], however, a literature survey revealed that such methods have mostly been used for analysis of botanicals and urine and plasma. Because EPH and PEPH are structurally similar and hydrophilic, several noticeable shortcomings, including poor separation, long elution times, and peak tailing, have been described when conventional methanol-water or acetonitrile-water mobile phases have been used.…”
Section: Introductionmentioning
confidence: 99%
“…These techniques have usually been applied to pharmacokinetics investigations and are not generally available in analytical laboratories, despite their high detection power. The method most widely used for assay of the isomers is high-performance liquid chromatography coupled with UV detection (LC-UV) [16][17][18][19], however, a literature survey revealed that such methods have mostly been used for analysis of botanicals and urine and plasma. Because EPH and PEPH are structurally similar and hydrophilic, several noticeable shortcomings, including poor separation, long elution times, and peak tailing, have been described when conventional methanol-water or acetonitrile-water mobile phases have been used.…”
Section: Introductionmentioning
confidence: 99%
“…The separation and quantification of EP and PE in different biological matrices using gas chromatography (GC), liquid chromatography (LC), and capillary electrophoresis have been extensively reported. In the authors' laboratory, a published method had been adopted for a few years in the analysis of EP and PE, which was based on liquid‐liquid extraction and heptafluorobutyric anhydride derivatization followed by gas chromatography–mass spectrometry analysis (HFBA‐GC‐MS) .…”
Section: Introductionmentioning
confidence: 99%
“…However, ephedrines are also used as a major active component in medications for the treatment of nasal congestion, asthma, and obesity . As a consequence of a widespread use of ephedrine, it has been necessary to develop analytical techniques for their reliable detection, including different hyphenated techniques, such as gas chromatography/mass spectrometry, gas chromatography/electron ionization mass spectrometry, and liquid chromatography/mass spectrometry/mass spectrometry . Another important characteristic of ephedrines is the existence on their structure of two chiral centers, with the corresponding four isomers: (1 S ,2 R )-(+)-ephedrine, (1 R ,2 S )-(−)-ephedrine, (1 S ,2 S )-(+)-pseudoephedrine, and (1 R ,2 R )-(−)-pseudoephedrine .…”
Section: Introductionmentioning
confidence: 99%